The role of the pathologist in tissue banking: European Consensus Expert Group Report - Bevilacqua, Generoso; Bosman, Fred; Dassesse, Thibaut; Höfler, Heinz; Janin, Anne; Langer, Rupert; Larsimont, Denis; Morente, Manuel M.; Riegman, Peter; Schirmacher, Peter; Stanta, Giorgio; Zatloukal, Kurt; et al. (Virchows Archiv, 2010)
Human tissue biobanking encompasses a wide range of activities and study designs and is critical for application of a wide range of new technologies (-“omics”) to the discovery of molecular patterns of disease and for implementation of novel biomarkers into clinical trials. Pathology is the cornerstone of hospital-based tissue biobanking. Pathologists not only provide essential information identifying the specimen but also make decisions on what should be biobanked, making sure that the timing of all operations is consistent with both the requirements of clinical diagnosis and the optimal preservation of biological products. This document summarizes the conclusions of a Pathology Expert Group Meeting within the European Biological and Biomolecular Research Infrastructure (BBMRI) Program. These recommendations are aimed at providing guidance for pathologists as well as for institutions hosting biobanks on how to better integrate and support pathological activities within the framework of biobanks that fulfill international standards.
Gesehen am 31.01.2023